COMPARATIVE EFFECTS OF PREOPERATIVE DEXAMETHASONE AND KETAMINE NEBULIZATION ON MINIMIZING NASOGASTRIC TUBE-RELATED COMPLICATIONS FOLLOWING LAPAROSCOPIC SURGERY - Mai Medani Elsaid Medani; Mohamed Zaki Shaaban Youssef; Ahmed Agwa; Muna Elamin Elfaki Elsheikh; Adel Hussein Dahshan; Sherif Atef Gomaa Aly (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Inserting a nasogastric (NG) tube is a common medical procedure, yet the resulting oropharyngeal discomfort is often underestimated. Typically, only standard lubricant jelly is used, with no additional analgesia, leading to suboptimal pain relief. This study compares the preoperative effectiveness of nebulized dexamethasone and ketamine in minimizing postoperative throat discomfort following NG tube insertion in patients undergoing laparoscopic surgery. Duration and place of study: This study was conducted in Hatta Hospital Dubai UAE from 01.06.2022 to 01.01.2024 Methodology: 150 patients with ASA physical status I–II, ages 18–65, who were scheduled for laparoscopic abdominal procedures under general anesthesia were enrolled in this prospective, study. Group A received 8 mg of nebulized dexamethasone, Group B received 50 mg of nebulized ketamine, and Group C received 5 ml of nebulized saline. Participants were randomly assigned to one of three groups. The NG tube was inserted after anesthesia induction. Patients were assessed for postoperative sore throat at recovery (0 hours), and then at 2, 8, 12, and 24 hours postoperatively. Data were analyzed using SPSS software version 26, with median, range, and qualitative data percentages and counts presented. A significance threshold of P < 0.05 was applied. Results: Both dexamethasone and ketamine nebulization significantly reduced the incidence of postoperative sore throat (POST) compared to saline. Dexamethasone demonstrated a greater reduction in POST than ketamine, with statistically significant differences at 0 hours (P < 0.001), 2 hours (P < 0.001), 8 hours (P < 0.001), 12 hours (P < 0.001), and 24 hours (P < 0.001). Conclusion: According to this study, preoperative nebulized dexamethasone reduces postoperative sore throat related to NG tube insertion more effectively than nebulized ketamine.